2019
DOI: 10.1107/s2053230x19015358
|View full text |Cite
|
Sign up to set email alerts
|

SpaB, an atypically adhesive basal pilin from the lactobacillar SpaCBA pilus: crystallization and X-ray diffraction analysis

Abstract: The SpaB pilin is recognized as the basal subunit of the sortase-dependent SpaCBA pilus, which is known to be produced by the Gram-positive Lactobacillus rhamnosus GG, a gut-adapted commensal advocated to have health benefits. Despite seeming to function as an archetypal basal pilin by serving as the terminal subunit in pilus assembly, SpaB also assumes an atypical role as a mucoadhesive protein. To shed light on the structural factors that contribute to this dual functional behaviour, a recombinant form of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Our antiserum blocking results also suggest that both the tip and backbone pilin contribute to collagen binding, while the base pilin does not. Previous reports of other Gram-positive pili have also shown that pilins other than the tip adhesin may have adherent abilities and participate in host cell binding ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 96%
“…Our antiserum blocking results also suggest that both the tip and backbone pilin contribute to collagen binding, while the base pilin does not. Previous reports of other Gram-positive pili have also shown that pilins other than the tip adhesin may have adherent abilities and participate in host cell binding ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 96%
“…Full-length L. rhamnosus GG SpaB (GG-SpaB FL ) protein (residues 33–205) was solubly produced in Escherichia coli ( von Ossowski et al., 2010 ), essentially as done previously for the GG-SpaA ( Singh et al., 2013 ), GG-SpaC ( Kant et al., 2016 ), GG-SpaD ( Chaurasia et al., 2015 ), and GG-SpaE ( Mishra et al., 2017 ) pilins. Since the GG-SpaB FL protein (~20 ​kDa) did not yield diffraction quality crystals, a truncated version (GG-SpaB C-trun ) missing a flexible portion of the C-terminal region (residues 185–205), but containing N-terminal hexahistidine tagging was cloned and solubly produced in E. coli as described previously ( Kumar Megta et al., 2019 ). Homogeneous and pure GG-SpaB C-trun protein (residues 31–184) yielded hexagonal crystals after the surface lysine methylation (SLM) treatment and the inclusion of 0.2 ​M MgCl 2 as an additive ( Kumar Megta et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Since the GG-SpaB FL protein (~20 ​kDa) did not yield diffraction quality crystals, a truncated version (GG-SpaB C-trun ) missing a flexible portion of the C-terminal region (residues 185–205), but containing N-terminal hexahistidine tagging was cloned and solubly produced in E. coli as described previously ( Kumar Megta et al., 2019 ). Homogeneous and pure GG-SpaB C-trun protein (residues 31–184) yielded hexagonal crystals after the surface lysine methylation (SLM) treatment and the inclusion of 0.2 ​M MgCl 2 as an additive ( Kumar Megta et al., 2019 ). The SLM treatment was done as described previously ( Kumar Megta et al., 2019 ; Rayment, 1997 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations